Determinants of Bank Failure in Asian Banks During The Covid-19 Pandemic - Fritma Salsabilah Ashofi; Abdul Mongid (AFRE (Accounting and Financial Review), 2024)
This research aims to determine the determining factors that led to bank failures in all Asian banks during the Covid-19 pandemic. The variables used to determine the factors of bank failure include Non-Performing Loans, Capital Adequacy Ratio, Equity to Total Assets, Total Assets, and L Assets to bank bankruptcy. This research uses a quantitative research design. The sample used is banking companies in Asia for 2017 - 2022. The data used in this research is secondary data from the financial reports of each Asian bank for the period 2017-2022. The data analysis technique used is panel data regression analysis. This research shows that Non-Performing Loans have a positive and significant effect on bank bankruptcy. Equity to Total Assets has a negative and significant impact on bank bankruptcy.DOI:https://doi.org/10.26905/afr.v7i1.11762